Penerapan Metode Trip Assignment dan Bunga Majemuk dalam Pembangunan Jalan Alternatif - A Nazil Munjazi; Mahendra , M. Oka (Jurnal Civil Engineering Study, 2025)
The increasing traffic volume in Panimbang District highlights the urgent need to assess the technical feasibility of constructing an alternative road as a long-term solution to potential congestion. This study aims to analyze the technical feasibility of an alternative road by applying the trip assignment method and traffic volume projection using compound interest formulas. Primary data were obtained through traffic surveys using the traffic counting method, and secondary data were collected from road geometry, population growth, and Gross Regional Domestic Product (GRDP) statistics. The analysis results show that the degree of saturation (DS) on the existing road is 0.283, with a projected increase to 0.401 over the next 10 years. The application of the trip assignment method shows that 42% of vehicles are likely to switch to the proposed alternative road, which is designed with a capacity of 5,100 pcu/hour and an operational speed of 42 km/h. The simulation indicates that the alternative road can reduce DS to 0.159 and decrease travel time from 42 minutes to 28 minutes. Moreover, the road offers more than 70% spare capacity to accommodate future traffic growth. Based on the parameters of DS, travel speed, and road capacity, the construction of an alternative road in Panimbang District is considered technically feasible.